2013
DOI: 10.1371/journal.pone.0060992
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitrogen and Glyphosate on Survival and Colonisation of Perennial Grass Species in an Agro-Ecosystem: Does the Relative Importance of Survival Decrease with Competitive Ability?

Abstract: The ecological success of a plant species is typically described by the observed change in plant abundance or cover, but in order to more fully understand the fundamental plant ecological processes, it is necessary to inspect the underlying processes of survival and colonization and how they are affected by environmental conditions. A general ecological hypothesis on the effect of environmental gradients on demographic parameters is proposed and tested. The hypothesis is that decreasing fitness or competitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…. Similarly, Damagaard et al [12] also reported that increasing levels of fertilizer enhanced the sprouting of cutting in Fesuca ovina.…”
Section: Sprouting Of Cuttingmentioning
confidence: 84%
“…. Similarly, Damagaard et al [12] also reported that increasing levels of fertilizer enhanced the sprouting of cutting in Fesuca ovina.…”
Section: Sprouting Of Cuttingmentioning
confidence: 84%
“…Furthermore, if plant abundance of perennial plants is measured several times during 210 a growth season, e.g. in spring and autumn (Damgaard, 2011;Damgaard et al, 2013;Damgaard et al, in 211 press), then the trait selection processes during summer growth may be estimated independently from the 212 trait selection processes during over-wintering and, consequently, allows the generation and testing of 213 temporal coexistence mechanisms (storage effects, Chesson, 2000). 214…”
mentioning
confidence: 99%